Projection of Rice Blast Diseases in West Java Region based on Climate Change Scenario - Aji Irsyam N. Sukarta; Yon Sugiarto; Yonny Koesmaryono (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2018)
Rice production in Indonesia has faced many challenges including disease outbreak leading to crop failure. Blast is a common disease, which is often found in paddy, that able to inhibit its growth and development. Here, we present simulation modeling to predict blast outbreak under climate change projection scenario in west Java, Indonesia. Two climate projections namely RCP4.5 and RCP8.5 were employed as input for EPIRICE epidemiological model. With this model we anaysed the potency of blast outbreak for 2021-2050. Then we compared the area of the projected blast with the output from current climate condition (1996-2005, as a baseline). Our results show that the potency of blast outbreak was in a low level under baseline. The area indicating a low level of outbreak was observed for both climate projections. Our findings revealed that a decreasing trend on the outbreak is expected for 2021-2050. However, an increased number of area having blast outbreak was observed especially in mountains region as many of 2%.day and 6%.day for RCP4.5 and RCP8.5, respectively.